2014
DOI: 10.1073/pnas.1401547111
|View full text |Cite
|
Sign up to set email alerts
|

The early rise and late demise of New Zealand’s last glacial maximum

Abstract: Significance We present here a comprehensive record of glaciation from a New Zealand valley glacier system covering the critical 15,000-y period from the local last glacial maximum (LGM) to near the end of the last ice age. This record from a key site in the midlatitude Southern Hemisphere shows that the largest glacial advance did not coincide with the coldest temperatures during this phase. We also show that the regional post-LGM ice retreat was very gradual, contrary to the rapid ice collapse wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 43 publications
7
60
2
Order By: Relevance
“…This suggests that the same forcing factors may have controlled the timing of glacial activity in both regions over the last glacial cycle and strongly suggests that glaciers advanced by at least 45 ka, or mid-MIS 3, well before the gLGM. Although this study focuses on chronology, it is worth highlighting that several studies found the limits relating to these advances to be as extensive, if not significantly more extensive, than those deposited during the gLGM (Glasser et al, 2011;Putnam et al, 2013b;Kelley et al, 2014;Rother et al, 2014;Doughty et al, 2015;Darvill et al, 2015;Schaefer et al, 2015).…”
Section: Evidence From the Compilation Of Exposure Agesmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the same forcing factors may have controlled the timing of glacial activity in both regions over the last glacial cycle and strongly suggests that glaciers advanced by at least 45 ka, or mid-MIS 3, well before the gLGM. Although this study focuses on chronology, it is worth highlighting that several studies found the limits relating to these advances to be as extensive, if not significantly more extensive, than those deposited during the gLGM (Glasser et al, 2011;Putnam et al, 2013b;Kelley et al, 2014;Rother et al, 2014;Doughty et al, 2015;Darvill et al, 2015;Schaefer et al, 2015).…”
Section: Evidence From the Compilation Of Exposure Agesmentioning
confidence: 99%
“…Cobb Valley -41 173 12 (9) (Shulmeister et al, 2005) Taramakau -43 171/172 34 (29) (Barrows et al, 2013) Arthur's Pass -43 172 5 (4) (Ivy-Ochs et al, 1999) Waimakariri -43 172 31 (29) (Rother et al, 2015) Rakaia Valley -43/-44 171/172 55 (46) (Shulmeister et al, 2010;Putnam et al, 2013a) Cameron glacier -43 171 10 (10) (Putnam et al, 2012) Franz Josef -43/-44 170 6 (6) (Barrows et al, 2007b) Rangitata Valley -43/-44 171 56 (51) (Rother et al, 2014) Pukaki -44 170/171 169 (159) (Schaefer et al, 2006;Putnam et al, 2010a;Kelley et al, 2014;Doughty et al, 2015;Schaefer et al, 2015) Ohau -44 170 91 (84) (Kaplan et al, 2013;Putnam et al, 2013b) Irishman Stream -44 170 33 (31) Cascade Plateau -44 168 19 (14) (Sutherland et al, 2007) Boundary Stream Tarn -44 170 10 (10) (Putnam et al, 2010b) Total within Last Glacial Cycle 531 (482) 37 Table 2. The timing of culminations in glacial advances identified from relative cumulative 4 probability density functions for New Zealand and Patagonia using the New Zealand 5 production rate of , and using the Patagonian production rate (PPR) of 6 Kaplan et al (2011) for Patagonia.…”
Section: New Zealandmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinn, Winkler, Salinger, & Haakensen, 2005;Oerlemans, 1997;Winkler et al, 2010), and because it is isolated from the major northern hemisphere ice sheets, it is an excellent location to examine inter-hemispheric synchrony or asynchrony of glaciations (e.g. Putnam et al, 2012;Rother et al, 2014). Terrestrial cosmogenic radionuclide studies of moraine boulders have unlocked the chronology of the largest advances in the last glacial cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Matukituki), which might have provided an alternate method of damming Wanaka drainage. This mechanism of lake damming via outwash fan is observed at modern lakes in New Zealand, such as Lake Pukaki (Evans et al, 2013), Lake Ohau (Rother et al, 2014) and Lake Tekapo (Maizels, 1989). The modern Clutha river incises through an older alluvial fan immediately to the SE of the Wanaka/Clutha confluence, and it is this fan that is presented as the best candidate for the damming of Lake Wanaka during deglaciation.…”
Section: Glacial Retreatmentioning
confidence: 88%